ARCHITECTURAL DESIGN AND WOODEN SRUCTURES OF TRADITIONAL OGAN ILIR BUILDINGS AS THE LOCAL CULTURAL WEALTH OF THE OGAN ILIR COMMUNITY. - Ade Ulansari; Iftahurrahmah Iftahurrahmah; Syarifuddin Syarifuddin (Sosiohumaniora, 2022)
South Sumatra has a lot of traditional houses across its region. Each house has its own characteristics. One notable design is houses built on stilts. In Ogan Ilir, especially Tanjung Batu, it is famous for the production of knock-down houses. Knock-down houses in Tanjung Batu are a stilt house with an architectural design that almost resembles a Limas house, only that these knock-down houses are specially designed to make it easy to disassemble and reassemble them elsewhere. This study aims to give a closer look at the design, structure and wood choices of knock-down houses that have become unique, cultural houses of Ogan Ilir people. This study will look at how the architectural design of the houses’ characteristics and wooden structures are adapted to the surrounding environment. This study was conducted qualitatively with an anthropological approach through ethnological techniques. To dig up information about knock-down houses, this was done through observation and data collection by conducting interviews and collecting written data such as journals and articles related to the topic. Observations and interviews were carried out in Tanjung Batu, which is the center for knock-down house craftsmen. The results obtained in this study are: (a) the daily activities of carpenters in the manufacture of knock-down houses, (b) tools and materials used in the construction of the knock-down houses, (c) sales of knock-down houses, (d) the development of wood tools and materials following the development of increasingly sophisticated technology, and (e) information about knock-down houses as a local, cultural building typical of Ogan Ilir.